Long non-coding RNAs regulated NF-κB signaling in cancer metastasis: Micromanaging by not so small non-coding RNAs - Ahmad, Shaniya; Abbas, Madiha; Ullah, Mohammad Fahad; Aziz, Moammir H.; Beylerli, Ozal; Alam, Majid Ali; Syed, Mansoor Ali; Uddin, Shahab; Ahmad, Aamir (Seminars in cancer biology, 2022)
Cancer metastasis is a major reason for the cancer-associated deaths and a role of long non-coding RNAs (lncRNAs) in cancer metastasis is increasingly being realized. Among the many oncogenic pathways, NF-κB signalling’s involvement in cancer metastasis as a key inflammation-regulatory transcription factor has been a subject of interest for long time. Accumulating data from in vitro as well as in vivo studies along with analysis of clinical cancer tissues points to regulation of NF-κB signalling by lncRNAs with implications toward the onset of cancer metastasis. LncRNAs FOXD2-AS1, KRT19P3 and the NF-κB interacting lncRNA (NKILA) associate with lymph node metastasis and poor prognosis of individual cancers. The role of epithelial-mesenchymal transition (EMT) in cancer metastasis is well known. EMT is regulated by NF-κB and regulation of NF-κB/EMT-induced metastasis by lncRNAs remains a hot topic of research with indications for such roles of lncRNAs MALAT1, SNHG15, CRNDE and AC007271.3. Among the many lncRNAs, NKILA stands out as the most investigated lncRNA for its regulation of NF-κB. This tumor suppressive lncRNA has been reported downregulated in clinical samples representing different human cancers. Mechanistically, NKILA has been consistently shown to inhibit NF-κB activation via inhibition of IκBα phosphorylation and the resulting suppression of EMT. NKILA is also a target of natural anticancer compounds. Given the importance of NF-κB as a master regulatory transcription factor, lncRNAs, as the modulators of NF-κB signaling, can provide alternate targets for metastatic cancers with constitutively active NF-κB.